Examining failure learning in online lending: Complete failure vs. incomplete failure - Ji-Wen Li (Public Library of Science (PLoS), 2021)
We examine the learning effects of borrowers’ failures in online lending. Based on funding ratios of borrowers’ loan listings in online lending, we first explore the role of failure degree in borrowers’ future funding performance. Further, we disaggregate borrowers’ funding failure into complete failure and incomplete failure, and compare theirs learning effects. Using a large sample of 610,000 online loan applications over six years from a Chinese leading online lending platform Renrendai, we use funding ratio to quantifiably measure each loan listing’s failure degree and conduct a series of tests. The results show that: (1) Borrowers’ failure degree of prior loan applications is negatively associated with one’s subsequent funding performance. (2) Borrowers’ complete failure cannot promote learning, while incomplete failure is good for future performance. (3) Both incomplete failure and complete failure interacted to influence the value of each type of experience and generate improved learning. Our results are robust across a variety of settings. The study sheds light for deeply understanding of failure learning phenomenon, and can also provide important implications for online lending managers to support successful financial transactions.